Fundamental analysis and discoiunted free cash flow valuation of stocks at Macedonian Stock Exchange - Zoran Ivanovski; Nadica Ivanovska; Zoran Narasanov (UTMS Journal of Economics, 2014)
We examine the valuation performance of Discounted Free Cash Flow Model (DFCF) at the Macedonian Stock Exchange (MSE) in order to determine if this model offer significant level of accuracy and relevancy for stock values determination. We find that stock values calculated with DCF model are very close to average market prices which suggests that market prices oscillate near their fundamental values. We can conclude that DFCF models are useful tools for the companies' enterprise values calculation on long term. The analysis of our results derived from stock valuation with DFCF model as well as comparison with average market stock prices suggest that discounted cash flow model is relatively reliable valuation tool that have to be used for stocks analyses at MSE.
Keywords: G1; G12; 330; valuation; securities; free cash flow; equity; stock-exchange